An economical processing technique to improve RAP inclusive concrete properties. (1st September 2017) - Singh, Surender; Ransinchung, G.D.; Kumar, Praveen
Highlights: A novel beneficiation method for treatment of RAP is introduced. Beneficiation by AB&AT method improved the mechanical properties of aggregates. Compressive, flexural, and split tensile strength of concrete increases significantly. Incorporations of RAP enhanced the durability properties of concrete. Abstract: The presence of asphalt film around Reclaimed Asphalt Pavement (RAP) aggregates has been reported as the main factor lowering the properties of RAP inclusive concrete. A novel Abrasion and Attrition (AB&AT) technique to improve the quality of RAP by removing the contaminant layers of dust and punching the asphalt film adhering to RAP aggregates is introduced in this paper. The effect of incorporating Dirty RAP (DRAP), Washed RAP (WRAP) and AB&AT treated RAP, on the fresh, mechanical and durability properties of concrete are also investigated and compared with each other. The mechanical properties of RAP aggregates were found to be increased significantly on processing with AB&AT method. Beneficiation of RAP by AB&AT method increased the compressive strength of concrete by 9.74% &12.71%, split tensile by 2.66% &12.21% and flexural strength by 6.05% & 8.55% as compared to WRAP and DRAP inclusive concrete. Incorporation of RAP into concrete mix improved workability & cohesiveness. Durability properties of concrete such as water absorption, initial rate of water absorption, total permeable voids and coefficient of water absorption were observed to be reduced for RAP inclusive concrete.